Angle-dependence of the magnetotransport and Anderson localization in a pressure-induced organic superconductor - Goddard, P; Tozer, S; Singleton, J; Ardavan, A; Bangura, A; Kurmoo, M (2003)
The conducting properties of the pressure-induced, layered organic superconductor (BEDT-TTF)(3)Cl-2 . 2H(2)O have been studied at 13.5 and 14.0 kbar using low temperatures, high magnetic fields and two-axis rotation. The observed negative magnetoresistance at 13.5 kbar can be explained by considering Anderson localization within the layers. Further application of pressure destroys the effects of localization.